Behavioral, Virologic, and Immunologic Factors Associated with the Acquisition and Severity of Mpox: A Tale of Africa and America - Dada, Michael; Enitan, Seyi; Akele, Richard; Edafetanure-Ibeh, Okeoghene; Omoare, Adesuyi; Dogonyaro, Banenat; Adetosoye, Aolat; Awelewa, Wilson; Dickson, Michael; Edafetanure-Ibeh, Faith (Jordan Medical Journal, 2025)
Background: Mpox (formerly monkeypox) has emerged as a critical public health issue worldwide, characterized by notable differences in acquisition and disease severity between Africa and the Americas. Understanding the interplay of behavioral, virologic, and immunologic factors is essential to addressing these disparities. Aim: This review examines the behavioral, virologic, and immunologic determinants influencing Mpox acquisition and severity, with a focus on regional variations in Africa and the Americas. Methodology: A narrative review was conducted using peer-reviewed articles, public health reports, and official guidelines published between 2019 and 2024. Key sources were identified via databases including PubMed, Scopus, and Google Scholar. Analysis centered on behavioral risk factors (e.g., sexual networks, wildlife exposure), virologic attributes (e.g., viral clades), and immunologic influences (e.g., vaccination status). Results: The findings reveal distinct regional differences in Mpox transmission dynamics and outcomes. In Africa, zoonotic transmission is prominent, compounded by poor hygiene and under-resourced healthcare systems. In the Americas, outbreaks are driven predominantly by human-to-human transmission within sexual networks, particularly among men who have sex with men (MSM), and international travel. Virologically, the Central African clade demonstrates greater virulence than the West African clade, which has predominated recent global outbreaks. Immunologically, limited smallpox vaccination coverage in younger African populations has increased vulnerability, while partial cross-protection from smallpox vaccines in the Americas has mitigated disease severity to some extent. Conclusion: Effective Mpox control necessitates region-specific public health strategies. Enhanced vaccination programs, improved healthcare infrastructure, and tailored interventions addressing behavioral and virologic drivers are critical. Global collaboration is imperative to mitigate Mpox's spread and burden while addressing socio-economic and epidemiological disparities.